071 Evaluation of participant recruitment strategies for a research project into a mental health and psychological wellbeing drop-in centre within great ormond street hospital (GOSH). (December 2018) - Ching, BCF; Tibber, MS; Catanzano, M; Bennett, S; Liang, H; Heyman, I; Shafran, R
Abstract : Background: Many children with physical illness also have emotional or behavioural difficulties. These may impact significantly on the individual and family and may have consequences on the management and course of the physical illness. Psychological assessments and interventions have the potential to improve both mental and physical health outcomes in young people in a hospital setting. Aims: This study is part of a broader project evaluating the provision of early intervention for mental health difficulties in the form of a Mental Health and Psychological Wellbeing Drop-in Centre situated in GOSH reception. As GOSH is a research hospital, understanding optimal recruitment strategies is of critical importance. In this study, we aimed to evaluate such strategies. Methods: Researchers and trained GOSH volunteers recruited participants in reception and outpatient clinics over the course of a month. Additionally, a public information talk was given as a means of promoting mental health. Researchers used a recruitment log to measure perceived interest in the project and explored the effects of varying the method, time, day and location of recruitment on the volume of participants consented. Results: Twenty six participants have been consented to date. Preliminary analyses suggest that there was no significant difference in volume of participants consented as a function of time or day, but indicate a potential benefit of recruiting from across multiple locations in parallel. Child friendly activities, such as colouring and stickers, promoted the research to younger children and allowed parents space to talk whilst their child was occupied. Conclusion: As an ongoing study, further analyses will be conducted with a larger sample. The findings will inform recruitment strategies employed throughout the broader research project, and a result, increase patient access to psychological support within the hospital. Additionally, the findings are of broader relevance to other research projects recruiting within the hospital.